Evaluation of the Antibacterial Activity of Zingiber officinale Extract against Enterobacter - Shahad Saad Alwan; Rihab Jumaah Mansoor; Huda Abdul Hameed (AlQalam Journal of Medical and Applied Sciences, 2025)
Zingiber officinale (ginger) is a medicinal herb known for its bioactive components with potential antibacterial properties. This study evaluates the antibacterial activity of aqueous and ethanolic extracts of ginger, sourced from Diyala, Iraq, against Enterobacter species. Extracts were prepared and tested in varying concentrations at the laboratories of the Department of Biology, College of Science, Diyala University. The results showed that Enterobacter was resistant to the aqueous extract at a concentration of 0.1 mg/mL. However, at 0.2 mg/ml, the bacteria showed sensitivity, with an inhibition zone of 2 cm, while o.3mg/mL resulted in a 5 cm inhibition zone. In contrast, the ethanolic extract demonstrated higher antibacterial activity: although Enterobacter remained resistant at 0.1 mg/mL, it was sensitive at 0.2 mg/mL (5 cm inhibition zone), and the inhibition zone increased to 6 cm at 0.3 mg/mL. Overall, ethanolic extracts exhibited greater antibacterial effectiveness than aqueous extracts. The antibacterial activity of ginger is influenced by factors such as extract concentration, extraction method, and bacterial strain type. While conventional antibiotics generally show higher effectiveness, ginger extracts may serve as a natural antibacterial agent, particularly in mild or supportive clinical applications. Based on these findings, ginger has potential as both a flavoring agent and a natural antibacterial compound.